The Science and Technology Labor Force The Value of Doctorate Holders and Development of Professional Careers - Gokhberg, Leonid; Shmatko, Natalia; Auriol, Laudeline; SpringerLink (Online service) (Cham : Springer International Publishing(Imprint), 2016)
This book provides an in-depth analysis of the demand for PhDs on the labor markets of twelve countries. The authors analyze the role of PhDs in the creation of innovation in a knowledge-based economy and examine economic issues such as the return on investment for the education and training of doctoral graduates. To provide a more comprehensive picture of the employment patterns, career paths and mobility of PhDs in selected countries, the book analyzes various data sources such as labor force surveys and censuses. The authors also develop survey approaches and output tables to collect data on the transition from school to work among PhDs. The book will be of interest to policymakers, companies and researchers responsible for research and innovation systems, as well as to doctoral students looking for a professional career outside the academic world.
Foreword -- Part I: The International Value of Doctorate Degrees on the Labor Market -- Part II: Doctorate Holders: Employment Outcome and Mobility -- Part III: Human Resources in Science and Technology and Their Professional Carrers -- Part IV: Conclusions.
Keywords: Labor economics; Education, Higher; Success in business; Economic policy; Labor Economics; Careers in Business and Mangagement; Educational Policy and Politics; Sociology of Education; R & D/Technology Policy